Immune mechanisms in hepatic and pulmonary fibrosis associated with telomeropathies in murine model and human disease - Gomes, Willian Robert (2024)
Telomeres are complex structures made up of repetitive sequences of nucleotides associated with proteins to form the ends of linear chromosomes. Telomere length reduces with each mitotic cycle and, once excessively short, they induce cells to engage senescence or apoptosis. Different pathogenic variants can lead to excessive shortening of telomeres, resulting in the development of telomeropathies. Hematopoietic stem cell failure (aplastic anemia) is one of the main clinical manifestations of telomeropathies, but patients might develop fibrotic responses in organs such as the lungs (pulmonary fibrosis) and liver (cirrhosis). Although there is evidence showing correlation between telomeric erosion and liver cirrhosis, the mechanisms involved in this process are not well understood. The present work aimed to evaluate the immune mechanisms involved in the development of hepatic and pulmonary fibrotic processes caused by telomeric shortening. For this, Terc-/- and Tert- /- knockout murine models were studied and wild-type animals with the same genetic background were evaluated as controls. Liver fibrosis was induced by controlled Schistosoma mansoni infection. After 12 weeks of infection, animals were sacrificed for sample collection. Liver fibrosis index was determined by Picro-Sirius Red, and phenotypic characterization of infiltrated macrophages was performed by immunohistochemistry. Bone marrow-derived macrophages were tested for their polarization capacity in vitro. In serum, the cytokine profile was evaluated by CBA to identify the inflammatory pathways involved. Additionally, patients with telomeropathies and pulmonary fibrosis and/or cirrhosis, diagnosed by imaging and/or biopsy, were also studied. The phenotypic characterization and stratification of subpopulations of T, B, NK lymphocytes, monocytes and dendritic cells in peripheral blood was performed by mass cytometry (CyTOF) and the serum cytokine profile was determined by Luminex in order to verify the differences displayed in the cellular and molecular immune profile in patients who develop fibrotic disease. Results show that Terc or Tert silencing causes changes in the immune response capacity in mice, especially in macrophages, which culminate in a reduction in the fibrotic response following the infection with S. mansoni. Patients present with pro-inflammatory subpopulations and a senescent phenotype, in addition to variations in cytokines, chemokines and growth factors caused by cytopenias. It is expected that the results will contribute to a better understanding of how telomeric dysfunctions influence the development of fibrotic processes, and that possible new therapeutic targets will be identified for the treatment of these complications.